Mediating and moderating effects of perceived social support on the relationship between discrimination and well-being: A study of South Koreans living in Japan - Park, Joonha; Joshanloo, Mohsen (Frontiers in Psychology, 2022)
We examined the relationship between discrimination and mental well-being among South Korean residents (N = 181) in Japan. The role of need for belonging (NTB) as a mediator and identification with one's group as a moderator of these associations were examined. Perceived social support was tested as both a potential moderator and mediator. We also included a measure of perceived in-group inclusion in the host society, the Circle of Ingroup Inclusion (CII), to examine its influence on the relationship between discrimination and well-being. Three types of coping styles-active constructive coping, passive constructive coping, and destructive coping-were controlled for in the analysis. Results showed that participants' educational level, socioeconomic status, and different coping styles predicted well-being; however, discrimination was the strongest (negative) predictor of well-being. Social support showed both moderation and mediating effects, suggesting that perceived social support not only buffers the negative effect of discrimination on well-being, but also partially explains the negative association between discrimination and well-being. NTB was not a significant mediator. Identification with one's ethnic group and perceived membership in one's group also had no effect on the relationship. The current study suggests that it is important to consider social support based on interpersonal relationships among members of minority groups in Japanese society. The psychological factors involved in acculturation processes may be different in different ethnic groups. This study calls for greater consideration of group-specific characteristics in understanding acculturation processes and interactions between groups in society.